A liberal theory of international justice - Altman, Andrew, 1950-; Wellman, Christopher Heath (Oxford : Oxford University Press, 2009)
This text advances a novel theory of international justice that combines the orthodox liberal notion that the lives of individuals are what ultimately matter morally with the putatively antiliberal idea of an irreducibly collective right of self-governance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International relations; International law; Justice; International relations -- Moral and ethical aspects